P2_11 Drop and give me ten - Youle, Oliver; Raymer, Katie; Jordan, Benjamin; Morris, Thomas (Physics Special Topics, 2013)
The press-up is commonly used for strength building purposes. This paper however calculates the amount of energy expended when performing a press-up to determine whether it is an effective exercise for burning calories. By considering the person’s centre of mass and the energetics of the system we calculate 342 Joules are required to perform a press-up.